2016
DOI: 10.1111/jai.13172
|View full text |Cite
|
Sign up to set email alerts
|

Length-weight relationships of freshwater fishes of the Alto Madre de Dios River (Manu Biosphere Reserve, Peru)

Abstract: Summary The present work provides the estimates of morphometric relationships for 22 native freshwater fish species (11 Characidae, five Loricariidae, two Heptapteridae, one Astroblepidae, one Crenuchidae, one Curimatidae and one Erythrinidae) collected in the Alto Madre de Dios River (Cuzco and Madre de Dios, Peru) in June 2012 using a mobile backpack electrofishing unit. These are the first length–weight relationships reported for 24 species, mostly endemic to the Amazonian basin. Knowledge regarding these b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 9 publications
(10 reference statements)
0
6
0
2
Order By: Relevance
“…The b values of N. gerreoides , S. scaber and T. theraps were comparable with previous findings (Deyrestani et al., ; Murty, ; Willing & Pender, ). The LWRs in fishes can be affected by a number of factors including season, habitat, area, degree of stomach fullness, gonad maturity, sex, health, preservation techniques, and differences in the observed length ranges of the captured specimens (Hossain et al., ; Li et al., ; Tobes, Miranda, Pino‐del‐Carpio, Araujo‐Flores, & Ortega, ), which were not accounted for in the present study. Because the sampling of the present study represents only 6 months and does not include seasonal and inter‐annual variability, thus the estimated LWR parameters are still tentative and are only reflect a snapshot picture of the population in this studied system.…”
Section: Discussionmentioning
confidence: 66%
“…The b values of N. gerreoides , S. scaber and T. theraps were comparable with previous findings (Deyrestani et al., ; Murty, ; Willing & Pender, ). The LWRs in fishes can be affected by a number of factors including season, habitat, area, degree of stomach fullness, gonad maturity, sex, health, preservation techniques, and differences in the observed length ranges of the captured specimens (Hossain et al., ; Li et al., ; Tobes, Miranda, Pino‐del‐Carpio, Araujo‐Flores, & Ortega, ), which were not accounted for in the present study. Because the sampling of the present study represents only 6 months and does not include seasonal and inter‐annual variability, thus the estimated LWR parameters are still tentative and are only reflect a snapshot picture of the population in this studied system.…”
Section: Discussionmentioning
confidence: 66%
“…During the presently reported study, isometric growth was determined between weight and length of the whole sample, and for females and males separately. For the same species, similar type of growth was reported by Gonçalves et al (1997) from the southern coast of Portugal (b = 2.81), by Santos et al (2002) from the Algarve coast (b = 3.02), by Türkmen and Akyurt (2003) from Iskenderun Bay, Turkey (b = 3.05), by Morey et al (2003) from the Balearic Islands and the Iberian coast (b = 3.03), by Mariani (2006) from Caprolace, Latina Province, Italy (b = 3.04), by Gökçe et al (2007) from the northern Aegean Sea (b = 3.10), by Keskin and Gaygusuz (2010) Even with an isometric type of growth the t-test in all these regions (statistically b = 3), the differences in b values can be due to a combination of one or more factors such as habitat, seasonal effect, degree of stomach fullness, gonad maturity and spawning period, health, preservation techniques, and differences in observed length ranges of the captured specimens (Erkoyuncu 1995, Li et al 2013, Hossain et al 2015, Tobes et al 2016, Saleh and Soegianto 2017.…”
Section: Discussionmentioning
confidence: 99%
“…A comparison with data from FishBase showed that the growth types (b values) of fish highly varied among species and locations (Froese and Pauly 2017). These differences in b values can be attributed to a combination of one or more factors including: habitat, area, seasonal effect, degree of stomach fullness, gonad maturity, sex, health, preservation techniques, and differences in the observed length ranges of the captured specimens (Li et al 2013, Hossain et al 2015, Tobes et al 2016. The results of presently reported study are useful for evaluation of the status of the investigated species.…”
mentioning
confidence: 89%